Feed intake, digestibility and nitrogen balance of West African dwarf goats fed maize offal and sorghum brewer's grains (2002)
Feed Intake, digestibility and nitrogen balance were determined in nine female West African dwarf (WAD) goats fed varying levels of maize offal (MO) and sorghum brewer’s grains (SBG) using a randomised block design. The diets did not significantly affect the dry matter Intake (DMI) or intake of crude protein (CP), neutral detergent fibre (NDF) and energy of the animals. The feed intake, nutrient digestibility and nitrogen balance of the animals were significantly (P <0.05) affected. However, digestibility and nitrogen balance increased with increasing levels of SBG in the diet Inclusion levels of 40% SBG and 24% MO in the diet favoured growth rate and the feed utilization. Since MO and SBG are locally available and devoid of human competition, their utilization in small ruminant nutrition will meet dietary requirements at a reduced feed cost and reduction in environmental pollution.